A Conservative Amino Acid Mutation in the Master Regulator FleQ Renders Pseudomonas aeruginosa Aflagellate - Jain, Ruchi (Public Library of Science, 2014)
Flagellar-based motility plays a critical role in Pseudomonas aeruginosa pathogenesis, influencing both the establishment of bacterial infection and the host's response to the pathogen. Nonetheless, aflagellate clinical strains are often isolated from acutely and chronically infected patients and include the virulent laboratory strain PA103. We determined that PA103's aflagellate phenotype is the result of a single amino acid change (G240V) in the master flagellar regulator, FleQ. This mutation, which lies just outside the Walker B box of FleQ, abrogates the ability of FleQ to positively regulate flagellar gene expression. Reversal of this seemingly conservative amino acid substitution is sufficient to restore swimming motility to PA103, despite the presence of mutations in other flagellar genes of PA103. We also investigated the consequences of restoring flagellar assembly on PA103 virulence. Although a negative correlation between flagellar assembly and Type 3 secretion system (T3SS) expression has been reported previously, we did not observe downregulation of T3SS expression or function in Fla+ PA103. Restoration of flagellar assembly did, however, amplify IL-1 signals measured during murine pulmonary infection and was associated with increased bacterial clearance. These experiments suggest that loss of flagellar motility may primarily benefit PA103 by attenuating pathogen recognition and clearance during acute infection.